(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Renal damage frequently complicates perinatal asphyxia. Renal vasoconstriction due to adenosine metabolite leads to a fall in glomerular filtration rate (GFR) and filtration fraction (FF). This might be inhibited by the nonspecific adenosine receptor antagonist, theophylline. Objective: To determine the efficacy of prophylactic theophylline in prevention of acute renal failure in term neonates exposed to perinatal asphyxia. Material and Methods: This descriptive case series was conducted at Department of Neonatology, The Children’s Hospital, Lahore for 6 months. Total 75 asphyxiated term infants were included through non-probability purposive sampling technique. Children received 5 mg/kg single dose of IV theophylline during first 24 hours of life. Fluid intake, urine output, serum creatinine was recorded on proforma. The data was analyzed using SPSS version 20. The efficacy of theophylline was calculated as frequency and percentage. Results: Mean age of presentation was 11.91±6.90 hours. Of the total 75 neonates, efficacy of theophylline i.e. prevented the neonates from developing AKI in 81.3% (n=61), while it had no effect in 18.7% (n=14). About 20% (n=15) patients died afterwards while 80% (n=60) patients were discharged home. Conclusions: Prophylactic theophylline is effective in prevention of acute kidney failure in neonates exposed to perinatal asphyxia.